High‐Rate Performance and Ultralong Cycle Life Enabled by Hybrid Organic–Inorganic Vanadyl Ethylene Glycolate for Lithium‐Ion Batteries. Issue 33 (8th October 2018) - Wang, Xinran; Bi, Xuanxuan; Zheng, Shili; Wang, Shaona; Zhang, Yi; Du, Hao; Lu, Jun
Abstract: Transition metal oxides (TMOs) possess high theoretical capacity and serve as promising anode candidates for lithium‐ion batteries. However, the intrinsic low conductivity handicaps the application of TMOs. Molecular modification by coupling TMOs structure with Li‐ion conductive polymer ligands can facilitate the kinetics of electrochemical lithiation/delithiation process. Herein, a proof‐of‐concept investigation on the Li‐ion storage capability by vanadyl ethylene glycolate (VEG) is achieved with the improvement of Li‐ion diffusion kinetics by modifiying the vanadium oxide with organic ligands. VEG demonstrates unprecedented advantage for fast rate capability, stable cycleability, and high capacity at both room temperarture (25 °C) and elevated temperature (60 °C). Abstract : A proof‐of‐concept investigation on the lithium‐ion storage capability by vanadyl ethylene glycolate (VEG) is achieved by modifying the inorganic vanadium oxide with organic ligands. By improving Li‐ion diffusion kinetics, VEG shows superior rate capability and stability, delivering an ultralong cycling lifespan at 1000 mA g −1 with a capacity of 550 mA h g −1 and 92% capacity retention after 2000 cycles.